Pollution source and chemicals structure of the water-soluble fractions in PM2.5 that induce apoptosis in China. (March 2023) - Ma, Huimin; Chen, Wenjing; Zhang, Qianyu; Wan, Cong; Mo, Yangzhi; Liu, Fei; Dong, Guanghui; Zeng, Xiaowen; Chen, Duohong; Yu, Zhiqiang; Li, Jun; Zhang, Gan
Highlights: WSOC played an important role in apoptosis than DCM-extracted fraction in PM2.5 . The aromatic and double-bond carbon structure in WSOC contributes to apoptosis. The WSOC from secondary products of motor vehicle exhaust is the risk drivers for apoptosis. The WSOC from coal and corn residues burning is the risk drivers for apoptosis. Abstract: Identify risk drivers is the key condition in air pollution control, and biological effect-directed analysis is the most commented method for combing chemical identify and human health. The water-soluble organic matter contained in PM2.5 plays an important role in human health, while it is also the most difficult to identify its chemical information. Exploring the structural characteristics and pollution sources of its key toxic components is the optimized strategy to meet this question. In this study, the induction of apoptosis by the water-soluble fractions (WSF) of PM2.5 samples collected in 10 major cities in China over a period of 1 year was observed in vitro in Beas-2b cells. Organic carbon structures were examined using nuclear magnetic resonance; air potential sources were identified using δ 13 C and 14 C isotopic markers. Apoptosis induction by WSF in PM2.5 was generally stronger in northern cities than in southern cities, and in winter than in summer. Organic compounds with aromatic and double-bond carbon structures from secondary products of motor vehicle exhausts, coal-derived emissions, and emissions derived from the burning of core residues may be primarily responsible for apoptosis induction by PM2.5 . Our results will contribute to understanding the toxic substances contained in WSF and provide basic data for accurate pollution control.